Review of the first WTO panel case on the Agreement on Safeguards : Korea - definitive safeguard measure on imports of certain daily products and its implications for the application of the Agreement. - Lee, Yong-Shik (1999)
Identifies important issues in the application of safeguards and provides resolutions to them for the first time since the settlement of the Agreement on Safeguards. Discusses important issues raised in the case and examines how the panel decisions could affect the application of the agreement.